A Rare Potential Pathogenic Variant in the BDNF Gene is Found in a Brazilian Patient with Severe Childhood-Onset Obesity - da Fonseca, Ana Carolina Proença (Diabetes Metab Syndr Obes, 2021)
BACKGROUND: Brain-derived neurotrophic factor (BDNF) is a pro-survival factor in the brain that also regulates energy balance. BDNF loss-of-function point mutations are responsible for haploinsufficiency, causing severe early-onset obesity. Up to date, only a few studies have sequenced this gene to search for rare mutations related to obesity. In this study, we aimed to investigate the prevalence of BDNF variants in a cohort of adults with severe obesity from Brazil. MATERIAL AND METHODS: This study comprised 201 adults with severe obesity (BMI ≥ 35.0 kg/m(2)) with onset during childhood- or adolescence/youth. As controls, 73 subjects with normal weight (18.5 ≤ BMI ≤ 24.9 kg/m(2)) were selected. The exclusion criteria were pregnancy, lactation, the use of medication to lose or gain weight, and the presence of symptoms suggestive of syndromic obesity (only for the case group). The coding region of the BDNF gene was screened by Sanger sequencing. Demographic, anthropometric, and blood pressure parameters were obtained from the participants as well as serum hormone and cytokines concentrations and biochemical values. RESULTS: As a result, three missense variants [p.(Thr2Ile), p.(Val66Met), and p.(Arg209Gln)] and four synonymous variants (p.Leu107=, p.Thr149=, p.Ala150=, and p.Ser213=) were identified. The p.(Arg209Gln) was predicted as pathogenic by all in silico algorithms used and was not observed in the control group. The individuals carrying the p.(Val66Met) mutated allele had higher waist circumference, HDL-cholesterol and MCP1 levels, and reduced risk of developing metabolic syndrome. CONCLUSION: We observed that the common BDNF p.(Val66Met) variant has influenced waist circumference, HDL-cholesterol, and MCP1 levels. This polymorphism has also a protective effect on metabolic syndrome susceptibility. Additionally, we described for the first time a rare potentially pathogenic BDNF variant in a Brazilian patient with severe obesity and childhood-onset.